GROTESQUE IN MEDIEVAL ART OF AZERBAIJAN - D., Muzaffarli (Journal of history, 2018)
The present article deals with the review of medieval Azerbaijani fine art, where grotesque used as an artistic method of exaggeration of the image. Canonical art of medieval printing miniature could not prevent miniature artists to express their attitude to the image. The most obvious grotesque images are seen in miniature of the 15th century, which were created in so-called «Turkomen style». Grotesque images flourish again in the 19th century in times of Gadjar dynasty. In conversation, the word grotesque usually means «strange», «fantastic», «eccentric» or «ugly», and thus is often used to describe strange or distorted forms, such as masks at a carnival or gargoyles at cathedrals. In addition, the concept of grotesque can refer to a specific kind of ornament, which combines visual and decorative motifs. Such combinations, as a rule, have a fancy or fantastic character.